Development of a Science Pocket Book Based of Mind Mapping for Class V Primary School - Juwantara, Ridho Agung; Harjanto, Ambyah; Puteri, Felicia Paras (STKIP PGRI Bandar Lampung, 2023)
The idea for developing this mind mapping-based pocket book originated from the unavailability of science learning resources that encourage and facilitate students to study independently outside of class hours. Mind mapping based pocket books are important for students to study independently because they are relatively small in size and include a mind map. This research aims to develop a pocket book based on mind mapping, to determine feasibility, response and effectiveness. This research is development research using the ADDIE model. The research results showed that the average validity score for the mind mapping based pocket book from the three validators was 93% in the very feasible category. The response assessment results from educators obtained a score of 93%, and from students it was 88.65%, both of which fell into the very appropriate category. The results of the product trial prove that this product development is effective and in accordance with the average score of 96% of the 10 students who took part in the product trial. This means that the pocket book based on mind mapping for science subjects is effective in maximizing the learning outcomes of class V students